2001
DOI: 10.1093/qjmed/94.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Insulin action and insulin secretion in polycystic ovary syndrome treated with ethinyl oestradiol/cyproterone acetate

Abstract: Polycystic ovary syndrome (PCOS) is associated with abnormalities of insulin action and insulin secretion. Ethinyl oestradiol/cyproterone acetate is a common agent used to treat the symptoms of PCOS, but its effects on insulin action and insulin pulsatility have not been examined. We investigated the relationship between insulin action and insulin secretion in 11 patients with PCOS, at diagnosis and after 3 months of treatment with ethinyl oestradiol/cyproterone acetate, and in 13 controls. Insulin action was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 21 publications
0
12
0
5
Order By: Relevance
“…Legro et al [7] reported a higher prevalence of insulin resistance in obese (64%) than in nonobese (20%) women with PCOS. Results of euglycemic hyperinsulinemic clamps have showed obese women with PCOS to have a higher insulin resistance [5,27–32]. In this study, the prevalence of insulin resistance was significantly higher in overweight patients than in patients of normal weight.…”
Section: Discussionmentioning
confidence: 44%
“…Legro et al [7] reported a higher prevalence of insulin resistance in obese (64%) than in nonobese (20%) women with PCOS. Results of euglycemic hyperinsulinemic clamps have showed obese women with PCOS to have a higher insulin resistance [5,27–32]. In this study, the prevalence of insulin resistance was significantly higher in overweight patients than in patients of normal weight.…”
Section: Discussionmentioning
confidence: 44%
“…Plasma insulin concentrations were constant in both of these studies indicating that the decrease in glucose tolerance was again due to a decrease in insulin sensitivity rather than a change in insulin levels/production. However, other studies performed in non-obese women showed no change in glucose tolerance and insulin sensitivity (Armstrong et al 2001; Cibula et al 2002; Elter et al 2002; Morin-Papunen et al 2003). This variation in results may suggest that metabolic consequences from COC treatment of PCOS depend on body type (Vrbikova and Cibula 2005).…”
Section: Metabolic Concernsmentioning
confidence: 71%
“…Apart from these positive effects on PCOS, OCPs are believed to slightly worsen insulin sensitivity 88-90, and for this reason, their use may aggravate the already impaired glucose metabolism of women with PCOS. However, studies estimating the role of OCPs on glucose tolerance 91 or insulin sensitivity [92][93][94][95][96][97][98] in women with PCOS have obtained conflicting results, and either no effect or a negative modification 91,94,96,97 was reported. There may be some negative influence on lipids also, and a low dose COCP may be preferable 99,100 .…”
Section: Management Of Pcosmentioning
confidence: 99%